Influence of Spike-Nosed Length on Aerodynamic Drag of a Wing-Projectile Model (Advances in Military Technology, 2022)
In this study, the effect of spike-nosed length on aerodynamic drag of a wing-projectile model was investigated at supersonic conditions. The projectile BK-13 with convex nose was selected for the study. The ratio of nose diameter and model diameter was fixed at around 0.34 while the ratio of the length of the nose and the model diameter was changed from 1.25 to 2.75. Numerical simulation with turbulent model k-ε was applied for flow structure around the model. The effect of mesh size and numerical models on the drag of the standard model was investigated. The study showed that numerical methods allow to obtain highly accurate drag coefficients. As the length of aerospike increases, the drag coefficient quickly decreases and obtains a minimum value at l/D = 2.0. The effect of spike-nosed length and velocity on flow pattern and drag of the model was explained in details in this study.
Keywords: aerospike; drag coefficient; flow fields; umerical methods